Time for health a campaign proposal on type 2 diabetes prevention for FIlipino adults ages 24 to 35 working in the business centers of Metro Manila - de los Reyes, Angelo Miguel M.; Sicat, Jose Manuel V. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Diabetes is one of the leading causes of death globally and is increasingly becoming more prevalent in the Philippines due to the Westernization of the Filipino diet, the urbanization of areas and the overdependence on technology that creates sedentary lifestyles ("2nd National Nutrition Summit"; Paz-Pacheco and Jimeno 2, Pingali 3). The disease, based on government statistics, is most prevalent in the middle to upper class Filipinos that reside in urban areas (Tan). Urban professionals working in business centers are identified to be one of the most vulnerable to type 2 diabetes due to the long working hours with very low occupational activity and the frequent consumption of fast food (Chen et al 29-40). Prevention is deemed as the most effective and most cost-efficient solution, especially a national health system that is still evolving (Napiza-Granada, Mela. Personal communication. 2018). This would entail moderating one's diet, being more physically active, and avoiding consumption of alcohol and tobacco products. However, even with the implementation of campaigns by the Department of Health, an upward trend of incidence is still observed. Furthermore, data from a conducted survey have shown that the visual communication materials employed by previous campaigns were not considered engaging or appealing enough to convince the target audience to adopt a healthier behavior. Survey respondents have also stated that one of the major factors that inhibits them from a healthy lifestyle is the lack of time - due to work - to be active and prepare healthier meals.

A campaign that not only raises awareness but also persuades people live healthily is needed. The campaign, titled Time for Health, is focused on leading the target audience towards a healthier lifestyle. The Transtheoretical Model is thus employed as it focuses on behavior and how it gradually changes with the aid of processes of change - or in this case a visual communication material. Each phase of Time of Health will employ an appropriate visual communication material that will ultimately lead the target audience to a more active and healthy lifestyle. The idea behind Time for Health is to provide a solution-based yet convenient and accessible approach towards building a diabetes-preventative lifestyle. The first phase uses print ads to raise awareness on type 2 diabetes and also promotes a mobile application called On the Go. The second phase focuses on the use of On The Go, which gives people the opportunity to purchase healthier food alternatives and reminds people to be physically active. The last phase employs promo-codes for users to acquire a discount on food and physical activity-related purchases. Social media influencers will also be used to promote the app and an event titled World Diabetes Day: Fun Run will also be launched to initiate discourse on diabetes prevention. Further research regarding the type 2 diabetes prevention campaigns can be conducted to target Filipinos that reside in rural areas of the country. Since for Health is focused on one's diet and physical activity, future campaigns can be mor focused on resolving the adherence of vices as they are considered risk factors of the diseases.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 67-72
Keywords: Type 2 Diabetes -- Prevention -- Philippines; Working class people -- Health -- Metropolitan Manila (Philippines); Health promotion -- Metropolitan Manila (Philippines)